Probiotics, synbiotics and berberine in Type 2 diabetes mellitus: A systematic review, meta-analysis, and molecular dynamics simulation study - Md. Shadin; Md. Shimul Bhuia; Mohammed Alfaifi; Faisal H. Altemani; Abdullah H. Altemani; Faisal Alsenani; Na’il Saleh; Muhammad Torequl Islam (PLoS ONE, 2026)
Background Type 2 diabetes mellitus is characterized by impaired regulation of blood glucose. Probiotics, synbiotics, and berberine (BBR) have been proposed as adjunctive interventions, but their overall effectiveness remains uncertain. Objective To evaluate the effects of these interventions on glycemic control and to explore a potential molecular interaction of BBR with a key carbohydrate-digesting enzyme. Methods A systematic review and meta-analysis of randomized controlled trials was conducted. Pooled effects were estimated for fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c) using random-effects models. A subgroup analysis compared probiotics with placebo. An exploratory computational analysis examined the interaction of BBR with α-glucosidase. Results More than 30 trials involving over 2,000 participants were included. The pooled analysis showed significant but modest reductions in FPG (−0.71 mmol·L ⁻ ¹) and HbA1c (−0.19%), with substantial between-study variability. Probiotics alone also reduced FPG (approximately −0.80 mmol·L ⁻ ¹) and HbA1c (approximately −0.21%) compared with placebo. Computational analysis indicated weaker enzyme binding for BBR than for the reference inhibitor acarbose. Conclusions Probiotics, synbiotics, and BBR provide statistically significant but clinically modest improvements in glycemic control. These findings support their use as adjunctive, rather than primary, therapeutic options and highlight the need for larger and longer trials with standardized interventions. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420251116387 , identifier CRD420251116387.